2022
DOI: 10.1155/2022/1046712
|View full text |Cite
|
Sign up to set email alerts
|

Bruguiera gymnorrhiza (L.) Lam. Fruit Accelerates Healing in Gastric Injury via the Regulation of the NF-κB Pathway

Abstract: Context. Bruguiera gymnorrhiza (L.) Lam. (BG), as a major species of mangroves, is also a traditional Chinese medicine, which has received attention for its anti-inflammatory and anticancer effects. However, the protective effect of BG on gastric injury is rarely studied. Objective. The present study aimed at the anti-inflammatory and antioxidant effects of the extract of Bruguiera gymnorrhiza (L.) Lam. fruit (BGF) on the gastric injury. Materials and Methods. The chemical components in the extract of BGF were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…rhynchopetala. These meroterpenoids have been classified as shikimate-meroterpenoids of the tricycloalternarene type (149)(150)(151)(152) and polyketidemeroterpenoids (131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147)(148), which contain tetraketide moieties derived from 3,5-dimethylors ellinic acid (131-143) and 6-methylsalicylic acid (144), and hexaketide moiety (145)(146)(147)(148), respectively.…”
Section: Meroterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…rhynchopetala. These meroterpenoids have been classified as shikimate-meroterpenoids of the tricycloalternarene type (149)(150)(151)(152) and polyketidemeroterpenoids (131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147)(148), which contain tetraketide moieties derived from 3,5-dimethylors ellinic acid (131-143) and 6-methylsalicylic acid (144), and hexaketide moiety (145)(146)(147)(148), respectively.…”
Section: Meroterpenoidsmentioning
confidence: 99%
“…Subsequently, Lin et al [149] observed that aqueous extracts from B. gymnorrhiza fruit also exhibited a protective effect against DSS-induced ulcerative colitis, and the mechanism may be associated with the attenuation of inflammation, activation of the Keap1/Nrf2 signaling pathway, and modulation of the gut microbiota. Furthermore, Zhang et al [150] reported that methanol extracts of B. gymnorrhiza fruits mitigate inflammation in gastric injury by activating the NF-κB pathway, thus conferring gastroprotective effects. Moreover, consumption of B. gymnorrhiza fruits has been shown to ameliorate systemic inflammations in obesity, increase circulating satiety hormones, reduce lipid profiles, elevate short-chain fatty acids levels, and promote weight loss [151].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%